PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN ( Studi Pada Kantor Perum Perumnas Regional 5 Semarang ) - Piliang, Fadel Muhammad Reza; Rahardja, Edy (Faculty of Economics and Business Diponegoro University, 2015)
Employee's performance can be measured through job satisfaction and organizational commitment.The Purpose of the research is to describe how the variables influence job satisfaction and organizational commitmen to employee performance of office Perum Perumnas Regional 5Semarang and to determine which variables are the dominant influences between the two variables.The population is every employee of office Perum Perumnas Regional 5 Semarang as much a65 employees. If the population is less than or close to a 100, then the population can be used as samples so that makes this a population research Arikunto (2006:134). Sampling technique of thisresearch is census, which is a technique of determining the sample when all the population is usedas samples. Data-testing technique used in the research include instrument testing (validity test, reliability test), classic assumption test (normality test, multicollinearity, heteroscedasticity test) multiple regression analysis, F-test, t-test, and coefficient of determination test (R2) by using SPSS16 application.The result shows that the work satisfaction and organizasional commitment influence positively and significantly to the employee performace. Value of determination coefisien or R square is 0,892, which means staff performance is affected by staff satisfication and organizational commitment as 89,2%.